Local structure of a switchable dielectric Prussian blue analogue. Issue 48 (29th November 2017) - Duncan, Helen D.; Beake, Edward O. R.; Playford, Helen Y.; Dove, Martin T.; Phillips, Anthony E.
Abstract : Two crystallographically similar phases of a dielectric framework material differ markedly in the rigidity of the cyanide framework. Abstract : The Prussian blue (cyanide-bridged, ordered double perovskite) analogue potassium imidazolium hexacyanoferrate, (C3 N2 H5 )2 K[Fe(CN)6 ], contains imidazolium cations encapsulated within a metal-cyanide framework. These are free to rotate in the intermediate- and high-temperature phases, but freeze into fixed orientations in the low-temperature phase. The phase transition between intermediate- and low-temperature phases thus causes a substantial change in this material's dielectric constant. However, the detailed cation dynamics, and in particular how they differ between intermediate- and high-temperature phases, remain unclear. We report here total neutron scattering measurements on a perdeuterated sample of this material. Reverse Monte Carlo modelling reveals that the intermediate-temperature phase is associated with a stiffening of the metal-cyanide framework compared to either of the other phases. This shows that the dynamics responsible for the phase transitions involve competition between the energetic penalty for bending the metal-cyanide links and the benefit of host–guest hydrogen bonding. Our results demonstrate both that disordered framework materials have important local structure that is not visible to Bragg scattering, and that there is a crucial link between this structure and the dynamics that give rise to exploitable electric properties.